A dinuclear cobalt complex catalyst, its preparation method and application

CN122912919APending Publication Date: 2026-10-16ANHUI CONCH MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611060138.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,这类催化剂普遍存在活性偏低、用量较大、反应温度和压力要求高、制备条件苛刻等不足,部分含钡催化剂还存在重金属毒性隐患

Benefits of technology

[0048] 1. This invention applies a binuclear cobalt complex derived from bis(3-substituted pyrazol-1-yl)methane to the ring-opening polymerization of ethylene oxide and fatty alcohols, representing the first application of a novel catalyst structure in this reaction;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912919A_ABST
    Figure CN122912919A_ABST
Patent Text Reader

Abstract

The application belongs to the field of fatty alcohol polyoxyethylene ether synthesis, and discloses a dinuclear cobalt complex catalyst, a preparation method and application thereof, the structure general formula of the catalyst is [Co2(mu-CH(3-R-pz)2)2Cl2], wherein R is -SCH3 or -SCF3, through the synergistic effect of the double cobalt center and the electronic effect of the substituent group, the application can efficiently catalyze the ring-opening polymerization of ethylene oxide and fatty alcohol under the condition of 80~110°C, and the fatty alcohol polyoxyethylene ether with narrow molecular weight distribution is synthesized, the PDI of the obtained fatty alcohol polyoxyethylene ether is less than or equal to 1.05, which is significantly better than the traditional alkali catalyst and mononuclear metal complex.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fatty alcohol polyoxyethylene ether synthesis, specifically relating to a binuclear cobalt complex catalyst, its preparation method, and its application. Background Technology

[0002] Fatty alcohol polyoxyethylene ether (AEO) is a type of nonionic surfactant produced by ring-opening polymerization of fatty alcohol and ethylene oxide under the action of a catalyst. Its key quality indicators, such as molecular weight distribution, free alcohol content and by-product composition, are highly dependent on the choice of catalytic system.

[0003] Currently, strong alkaline catalysts such as potassium hydroxide, sodium hydroxide, or sodium methoxide are commonly used in industry. These catalysts carry out ethoxylation reactions via anionic polymerization mechanisms. Because the acidity of the starting fatty alcohol is relatively similar to that of the ethoxylated product, a rapid proton exchange equilibrium exists within the system. This results in the reactivity of the starting fatty alcohol being much lower than that of the intermediate alcohol ether. A significant induction period occurs in the early stages of the reaction, leading to a wide molecular weight distribution of the final product, containing a large amount of unreacted free fatty alcohol and high addition number polyethylene glycol byproducts. This wide molecular weight distribution results in a broad cloud point range, poor wetting, penetration, and detergency of the AEO product. Excessive free alcohol content not only reduces raw material utilization but also imparts a distinctive odor to the product, limiting its application in personal care, textile auxiliaries, and other fields. Furthermore, the residue from the strong alkaline catalyst requires acid neutralization and adsorption removal, generating saline wastewater and solid waste, increasing post-treatment processes and environmental burden.

[0004] To overcome the aforementioned drawbacks of alkaline catalysis, various catalysts designed to achieve narrow molecular weight distributions have been developed. Among these, alkaline earth metal catalysts, such as oxides, hydroxides, or alkoxy compounds of barium and strontium, can undergo ethoxylation via a coordination-intercalation mechanism, suppressing proton exchange to some extent and yielding AEOs with lower free alcohol content and narrower molecular weight distributions. However, these catalysts generally suffer from low activity, large dosage requirements, stringent reaction temperature and pressure requirements, and demanding preparation conditions. Some barium-containing catalysts also pose a risk of heavy metal toxicity. Solid base or solid acid catalysts, represented by hydrotalcite, hydrotalcite-like compounds, and composite metal oxides, are easy to separate from the product, but it is difficult to simultaneously achieve optimal catalytic activity, selectivity, and long-term operational stability. While Lewis acids such as boron trifluoride can yield narrow-distribution products, they cause severe equipment corrosion and readily generate the carcinogen dioxane, limiting their industrial application. Other amine and bimetallic cyanide catalytic systems have been reported, but they often fail to simultaneously meet the requirements for catalytic activity, narrow distribution performance, and cost.

[0005] In summary, existing catalyst systems still struggle to simultaneously achieve high reactivity, narrow molecular weight distribution, low byproduct formation, and environmental friendliness under mild conditions. Therefore, it is still necessary to develop novel catalysts to meet the high-quality and green production requirements of fatty alcohol polyoxyethylene ethers. Summary of the Invention

[0006] The purpose of this invention is to provide a binuclear cobalt complex catalyst and its preparation method. The catalyst has the general structural formula [Co2(μ-CH(3-R-pz)2)2Cl2] (R = -SCH3 or -SCF3). It utilizes the synergistic effect of the two cobalt centers and the electronic effect of the substituents to efficiently catalyze the ring-opening polymerization of ethylene oxide and fatty alcohols under mild conditions, thereby obtaining products with a narrow molecular weight distribution.

[0007] Another objective of this invention is to provide the application of the aforementioned binuclear cobalt complex catalyst in the preparation of narrowly distributed fatty alcohol polyoxyethylene ethers.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] This invention provides a binuclear cobalt complex catalyst, which is composed of a binuclear cobalt complex supported on an inorganic support. The general structural formula of the binuclear cobalt complex is: [Co2(μ-CH(3-R-pz)2)2Cl2], and its molecular structure is shown below:

[0010] ;

[0011] In the formula, R is either -SCH3 or -SCF3;

[0012] The carrier is fluorapatite, the particle size of the carrier is 50~200 nm, and the cobalt loading is 3~10 wt% of the carrier mass.

[0013] This invention provides a method for preparing the above-mentioned binuclear cobalt complex catalyst, the method comprising the following steps:

[0014] 1) Under inert gas protection, 3-bromopyrazole was dispersed in a solvent, and sodium thiolate was added to carry out a nucleophilic substitution reaction. After post-treatment, alkylthiopyrazole was obtained.

[0015] 2) In a solvent, alkylthiopyrazole and dibromomethane were subjected to an N-alkylation reaction in the presence of sodium hydroxide aqueous solution and tetrabutylammonium bromide, and after post-treatment, CH2(3-R-pz)2 was obtained.

[0016] 3) CH2(3-R-pz)2 is dispersed in a solvent, and then n-butyllithium is added to carry out a deprotonation reaction to generate [CH(3-R-pz)2]. -Then [CH(3-R-pz)2] - Coordination assembly reaction with cobalt salt in solvent was carried out, and the product was filtered, washed and dried to obtain binuclear cobalt complex;

[0017] 4) Fluoroapatite is degassed under vacuum, and then the binuclear cobalt complex is dispersed in a solvent under inert gas protection. Fluoroapatite is added for loading to obtain the binuclear cobalt complex catalyst.

[0018] The inert gas is one or more of nitrogen or argon.

[0019] In step 1), the sodium thiolate is either sodium methanethiol or sodium trifluoromethanethiol.

[0020] In step 1), the molar ratio of 3-bromopyrazole, sodium methanethiol, and solvent in the nucleophilic substitution reaction is 1:1~10:1~30, the reaction temperature is 40~100℃, and the reaction time is 4~12h.

[0021] In step 2), the molar ratio of 3-alkylthiopyrazole, sodium hydroxide, tetrabutylammonium bromide and dibromomethane is 1:1~10:0.01~0.1:0.1~5.

[0022] In step 2), the N-alkylation reaction is carried out at room temperature for 6 to 24 hours.

[0023] In step 3), the molar ratio of CH2(3-R-pz)2, solvent and n-butyllithium in the deprotonation reaction is 1:200~500:1~10. The reaction conditions are as follows: in an anhydrous and oxygen-free glove box under nitrogen protection, the temperature is cooled to -60~-90℃, and n-butyllithium solution is added dropwise with stirring. After the addition is complete, the temperature is maintained at -60~-90℃ and stirred for 30 minutes. Then, the temperature is naturally raised to room temperature and stirring is continued for 1 hour.

[0024] In step 3), the [CH(3-R-pz)2] in the coordination assembly reaction - The molar ratio of cobalt salt to solvent is 1:1 to 10:1 to 200, the reaction time is 6 to 24 hours, and the reaction temperature is room temperature.

[0025] The cobalt salt is one or more of the following: cobalt chloride, cobalt nitrate, or cobalt sulfate.

[0026] According to a specific embodiment of the present invention, preferably, in step 4), the temperature of vacuum degassing is 100~200℃ and the time is 1~5h.

[0027] In step 4), the load treatment is carried out at room temperature for 6 to 24 hours.

[0028] In steps 1) to 4), the solvent is one or more of toluene, DMF, n-hexane, or THF.

[0029] The inert gas is one or more of nitrogen or argon.

[0030] The present invention also provides the application of the above-mentioned binuclear cobalt complex catalyst in the preparation of narrowly distributed fatty alcohol polyoxyethylene ethers.

[0031] A method for preparing narrowly distributed fatty alcohol polyoxyethylene ether, the method comprising the following steps:

[0032] A fatty alcohol and a binuclear cobalt complex catalyst were placed in a reaction vessel, and ethylene oxide was introduced to carry out a free radical reaction. After the reaction was completed, the narrow distribution fatty alcohol polyoxyethylene ether was obtained through post-treatment.

[0033] The amount of the binuclear cobalt complex catalyst used is 0.1% to 5.0% of the fatty alcohol.

[0034] The fatty alcohol is one or more C6-C18 alcohols, and its molecular structural formula is shown below:

[0035] ;

[0036] Where R is either H or CH3; n is a positive integer between 3 and 9.

[0037] The fatty alcohol polyoxyethylene ether has the following molecular structural formula;

[0038] ;

[0039] Where R is either H or CH3; n is a positive integer between 3 and 9; and m is a positive integer between 1 and 50.

[0040] The synthesis reaction equation for the fatty alcohol polyoxyethylene ether is shown below:

[0041] ;

[0042] Where R is either H or CH3; n is a positive integer between 3 and 9; and m is a positive integer between 1 and 50.

[0043] The free radical reaction includes an initiation stage and a main reaction stage. In the initiation stage, ethylene oxide is introduced at 60-80°C to fully initiate the fatty alcohol. The mass of EO added in the initiation stage is 10-15% of the total EO. In the main reaction stage, the temperature is raised to 90-110°C, and the remaining ethylene oxide is introduced at a constant rate to maintain the free EO concentration in the system below 5 wt%. The mass of EO added in the main reaction stage is all the remaining EO.

[0044] The molar ratio of the fatty alcohol to ethylene oxide is 1:1 to 50.

[0045] The pressure during the initiation stage is 0.10~0.30 MPa, and the pressure during the main reaction stage is 0.15~0.40 MPa.

[0046] The obtained fatty alcohol polyoxyethylene ether has a molecular weight distribution (PDI) ≤ 1.05 and a platinum-cobalt color intensity < 20.

[0047] Compared with the prior art, the present invention has the following advantages:

[0048] 1. This invention applies a binuclear cobalt complex derived from bis(3-substituted pyrazol-1-yl)methane to the ring-opening polymerization of ethylene oxide and fatty alcohols, representing the first application of a novel catalyst structure in this reaction;

[0049] 2. In this invention, two cobalt atoms are bridged by two deprotonated pyrazolium methane ligands, forming a stable binuclear structure. The two cobalt centers work synergistically: one cobalt center enhances the electrophilicity of the ethylene oxide monomer through Lewis acid activation; the other cobalt center stabilizes the growth chain end through terminal chlorine or alkoxide bridging. This dual-site connection allows for a better match between chain initiation and chain growth rates, effectively suppressing chain transfer side reactions. The product PDI ≤ 1.05, significantly superior to the PDI > 1.15 of traditional base catalysts and mononuclear metal complexes.

[0050] 3. A methylthio group (-SCH3) or a trifluoromethylthio group (-SCF3) is introduced at the 3-position of the pyrazole ring of the ligand. The Lewis acidity of the cobalt center is finely controlled through the electronic effect of the sulfur atom (electron donation or electron withdrawal). At the same time, the ligand field strength is enhanced, making the binuclear structure more stable, which is conducive to catalytic conversion under mild conditions. The strong electron-withdrawing effect of the trifluoromethylthio group further improves the catalytic selectivity.

[0051] 4. The catalytic reaction can be carried out at 60~110°C, significantly reducing energy consumption and side reactions, and the product color is <20. The catalyst can be recovered through filtration and can be recycled more than 5 times while maintaining its activity, meeting the requirements of green chemistry. Attached Figure Description

[0052] Figure 1 The GPC spectrum for the first cycle synthesis of fatty alcohol polyoxyethylene ether in Application Example 1. Detailed Implementation

[0053] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0054] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0055] Example 1

[0056] A method for preparing a binuclear cobalt complex catalyst, specifically including the following steps:

[0057] 1) Under nitrogen protection, 1.0 mol of 3-bromopyrazole was dissolved in 1 L of anhydrous DMF, and 1.2 mol of sodium methanethiol was added. The mixture was heated to 80 °C and stirred for 8 h. After cooling to room temperature, the solution was poured into 2 L of ice water and extracted three times with 500 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The residue was then distilled under reduced pressure at 88 °C and 5 mmHg to obtain 3-methylthiopyrazole in 81% yield.

[0058] 2) In a 2 L round-bottom flask, add 2.0 mol of 3-methylthiopyrazole, 1.5 L of toluene, a 50 wt% NaOH aqueous solution containing 2.0 mol of NaOH, 0.10 mol of tetrabutylammonium bromide, and 1.0 mol of dibromomethane. Stir vigorously at room temperature for 12 h, allow to stand, separate the liquids, wash the organic phase three times with 300 mL of deionized water, dry with anhydrous sodium sulfate, filter, remove toluene by vacuum distillation, recrystallize the residue from ethanol to give CH2(3-SCH3-pz)2, yield 88%;

[0059] 3) In a nitrogen glove box, 10 mmol CH2(3-SCH3-pz)2 was dissolved in 100 mL of anhydrous THF, cooled to -78°C, and 4.0 mL of 2.5 M n-butyllithium hexane solution was added dropwise. The mixture was stirred at -78°C for 30 min, then allowed to rise naturally to room temperature and stirred for 1 h. This solution was then added dropwise to 40 mL of THF suspension containing 10 mmol of anhydrous CoCl2. The mixture was stirred at room temperature for 12 h, filtered, and the solid was washed three times with 20 mL of anhydrous THF and 20 mL of anhydrous n-hexane. The solid was then dried under vacuum for 12 h to obtain a binuclear cobalt complex with a yield of 76%. The Co content was determined by ICP-OES to be 17.32%, and the theoretical Co content was 17.55%.

[0060] 4) Take 10.0 g of fluorapatite with a particle size of 80 nm, wherein the specific surface area of ​​the fluorapatite is 120 m². 2 / g, degassed under vacuum at 150℃ for 2 h, and under nitrogen protection, 2.0 g of the binuclear cobalt complex was dissolved in 100 mL of anhydrous toluene, and the vacuum-degassed fluorapatite was added. The mixture was stirred at room temperature for 12 h, centrifuged, and the solid was washed three times with 30 mL of anhydrous toluene. The solid was then dried under vacuum at 80℃ for 12 h to obtain the binuclear cobalt complex catalyst. The Co loading was determined to be 5.2 wt% by ICP-OES.

[0061] Example 2

[0062] A method for preparing a binuclear cobalt complex catalyst, specifically including the following steps:

[0063] 1) Under nitrogen protection, 1.0 mol of 3-bromopyrazole was dissolved in 1 L of anhydrous DMF, and 1.2 mol of sodium trifluoromethylthiol was added. The mixture was heated to 80 °C and stirred for 8 h. After cooling to room temperature, the solution was poured into 2 L of ice water and extracted three times with 500 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The residue was then distilled under reduced pressure at 88 °C and 5 mmHg to obtain 3-trifluoromethylthiolpyrazole in 82% yield.

[0064] 2) In a 2 L round-bottom flask, add 2.0 mol of 3-trifluoromethylthiopyrazole, 1.5 L of toluene, a 50 wt% NaOH aqueous solution containing 2.0 mol of NaOH, 0.10 mol of tetrabutylammonium bromide, and 1.0 mol of dibromomethane. Stir vigorously at room temperature for 12 h, allow to stand, separate the liquids, wash the organic phase three times with 300 mL of deionized water, dry with anhydrous sodium sulfate, filter, remove toluene by vacuum distillation, recrystallize the residue from ethanol to give CH2(3-SCF3-pz)2, yield 86%;

[0065] 3) In a nitrogen glove box, 10 mmol CH2(3-SCF3-pz)2 was dissolved in 100 mL of anhydrous THF, cooled to -78°C, and 4.0 mL of 2.5 M n-butyllithium hexane solution was added dropwise. The mixture was stirred at -78°C for 30 min, then allowed to rise naturally to room temperature and stirred for 1 h. This solution was then added dropwise to 40 mL of THF suspension containing 10 mmol of anhydrous CoCl2, stirred at room temperature for 12 h, filtered, and the solid was washed three times with 20 mL of anhydrous THF and 20 mL of anhydrous n-hexane. The solid was then dried under vacuum for 12 h to obtain a binuclear cobalt complex with a yield of 74%. The Co content was determined by ICP-OES to be 13.08%, and the theoretical Co content was 13.34%.

[0066] 4) Take 10.0 g of fluorapatite with a particle size of 80 nm, wherein the specific surface area of ​​the fluorapatite is 120 m². 2 / g, degassed under vacuum at 150℃ for 2 h, and under nitrogen protection, 2.0 g of the binuclear cobalt complex was dissolved in 100 mL of anhydrous toluene, and the vacuum-degassed fluorapatite was added. The mixture was stirred at room temperature for 12 h, centrifuged, and the solid was washed three times with 30 mL of anhydrous toluene. The solid was then dried under vacuum at 80℃ for 12 h to obtain the binuclear cobalt complex catalyst. The Co loading was determined to be 4.8 wt% by ICP-OES.

[0067] Example 3

[0068] A method for preparing a binuclear cobalt complex catalyst, specifically including the following steps:

[0069] 1) Under nitrogen protection, 2.0 mol of 3-bromopyrazole was dissolved in 1.8 L of anhydrous DMF, and 2.4 mol of sodium methanethiol was added. The mixture was heated to 85 °C and stirred for 10 h. After cooling to room temperature, the solution was poured into 2 L of ice water and extracted three times with 500 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The residue was then distilled under reduced pressure at 90 °C and 5 mmHg to obtain 3-methylthiopyrazole in 82% yield.

[0070] 2) In a 2 L round-bottom flask, add 1.5 mol of 3-methylthiopyrazole, 1.2 L of toluene, a 50 wt% NaOH aqueous solution containing 1.65 mol of NaOH, 0.075 mol of tetrabutylammonium bromide, and 0.75 mol of dibromomethane. Stir vigorously at room temperature for 14 h, allow to stand, separate the liquids, wash the organic phase three times with 250 mL of deionized water, dry with anhydrous sodium sulfate, filter, remove toluene by vacuum distillation, recrystallize the residue from ethanol to give CH2(3-SCH3-pz)2, yield 86%;

[0071] 3) In a nitrogen glove box, 10 mmol CH2(3-SCH3-pz)2 was dissolved in 100 mL of anhydrous THF, cooled to -78°C, and 4.4 mL of 2.5 M n-butyllithium hexane solution was added dropwise. The mixture was stirred at -78°C for 40 min, then allowed to rise naturally to room temperature and stirred for 1.5 h. This solution was then added dropwise to 50 mL of THF suspension containing 10 mmol of anhydrous CoCl2, stirred at room temperature for 12 h, filtered, and the solid was washed three times with 20 mL of anhydrous THF and 20 mL of anhydrous n-hexane. The solid was then dried under vacuum for 12 h to obtain a binuclear cobalt complex with a yield of 76%. The Co content was determined by ICP-OES to be 17.28%, and the theoretical Co content was 17.55%.

[0072] 4) Take 10.0 g of fluorapatite with a particle size of 80 nm, wherein the specific surface area of ​​the fluorapatite is 120 m². 2 / g, degassed under vacuum at 160℃ for 2 h, and under nitrogen protection, 2.2 g of the binuclear cobalt complex was dissolved in 100 mL of anhydrous toluene, and the vacuum-degassed fluorapatite was added. The mixture was stirred at room temperature for 12 h, centrifuged, and the solid was washed three times with 30 mL of anhydrous toluene. The solid was then dried under vacuum at 80℃ for 12 h to obtain the binuclear cobalt complex catalyst. The Co loading was determined to be 5.5 wt% by ICP-OES.

[0073] Example 4

[0074] A method for preparing a binuclear cobalt complex catalyst, specifically including the following steps:

[0075] 1) Under nitrogen protection, 0.5 mol of 3-bromopyrazole was dissolved in 500 L of anhydrous DMF, and 0.55 mol of sodium trifluoromethylthiol was added. The mixture was heated to 70 °C and stirred for 12 h. After cooling to room temperature, the solution was poured into 2 L of ice water and extracted three times with 500 mL of ethyl acetate. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation. The residue was then distilled under reduced pressure at 88 °C and 5 mmHg to obtain 3-trifluoromethylthiolpyrazole in 78% yield.

[0076] 2) In a 2 L round-bottom flask, add 0.5 mol of 3-trifluoromethylthiopyrazole, 0.4 L of toluene, a 50 wt% NaOH aqueous solution containing 0.55 mol of NaOH, 0.025 mol of tetrabutylammonium bromide, and 0.25 mol of dibromomethane. Stir vigorously at room temperature for 10 h, allow to stand, separate the liquids, wash the organic phase three times with 300 mL of deionized water, dry with anhydrous sodium sulfate, filter, remove toluene by vacuum distillation, recrystallize the residue from ethanol to give CH2(3-SCF3-pz)2, yield 87%;

[0077] 3) In a nitrogen glove box, 10 mmol CH2(3-SCF3-pz)2 was dissolved in 100 mL of anhydrous THF, cooled to -78°C, and 4.0 mL of 2.5 M n-butyllithium hexane solution was added dropwise. The mixture was stirred at -78°C for 30 min, then allowed to rise naturally to room temperature and stirred for 1 h. This solution was then added dropwise to 40 mL of THF suspension containing 10 mmol of anhydrous CoCl2, stirred at room temperature for 12 h, filtered, and the solid was washed three times with 20 mL of anhydrous THF and 20 mL of anhydrous n-hexane. The solid was then dried under vacuum for 12 h to obtain a binuclear cobalt complex with a yield of 74%. The Co content was determined by ICP-OES to be 13.08%, and the theoretical Co content was 13.34%.

[0078] 4) Take 10.0 g of fluorapatite with a particle size of 80 nm, wherein the specific surface area of ​​the fluorapatite is 120 m². 2 / g, degassed under vacuum at 150℃ for 2 h, and under nitrogen protection, 2.0 g of the binuclear cobalt complex was dissolved in 100 mL of anhydrous toluene, and the vacuum-degassed fluorapatite was added. The mixture was stirred at room temperature for 12 h, centrifuged, and the solid was washed three times with 30 mL of anhydrous toluene. The solid was then dried under vacuum at 80℃ for 12 h to obtain the binuclear cobalt complex catalyst. The Co loading was determined to be 4.8 wt% by ICP-OES.

[0079] Comparative Example 1

[0080] This comparative example uses KOH catalyst.

[0081] Comparative Example 2

[0082] This comparative example uses a cobalt acetylacetone catalyst.

[0083] Comparative Example 3

[0084] A method for preparing a ligand catalyst without -SCH3 includes the following steps:

[0085] The difference between Comparative Example 1 and Example 1 is that step 1) is omitted, and 3-methylthiopyrazole in step 2) is replaced with pyrazole. The complex obtained in step 3) has the general structural formula [Co2(μ-CH(pz)2)2Cl2].

[0086] Application Example 1

[0087] A fatty alcohol polyoxyethylene ether C 18 The preparation method of AEO10 specifically includes the following steps:

[0088] 1 mol of octadecyl alcohol and 5.4 g of the catalyst described in Example 1 were added to a 2 L high-pressure reactor. After sealing, the reactor was purged with nitrogen three times. The temperature was raised to 80 °C with stirring. During the initiation stage, 44 g of ethylene oxide was introduced over 20 min to fully initiate the fatty alcohol. After the system temperature slowly rose to 100 °C, the remaining 396 g of ethylene oxide was added over 2 hours. The reactor was allowed to mature for 30 min, then vacuum devolatilized at 100 °C for 30 min. The reactor was then cooled to below 60 °C to release the pressure and was filtered to recover the catalyst. The recovered catalyst was washed with anhydrous ethanol and dried at 80 °C for direct use in the next batch of synthesis. The reactor was cycled a total of 10 times.

[0089] Application Example 2

[0090] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0091] Add 1 mol C to a 2 L high-pressure reactor12 With C 14 A mixture of alcohols, wherein C 12 alcohols and C 14 The molar ratio of alcohols was 3:1. 5.4 g of the catalyst described in Example 1 was added, sealed, and purged with nitrogen three times. The mixture was heated to 80°C with stirring. 44 g of ethylene oxide was introduced during the initiation stage, and the addition was completed in 20 min to fully initiate the fatty alcohol. After the system temperature slowly rose to 100°C, the remaining 396 g of ethylene oxide was added, and the addition was completed in 2 hours. The mixture was allowed to mature for 30 min, then vacuum devolatilized at 100°C for 30 min. The temperature was then lowered to below 60°C to release the pressure, and the catalyst was recovered by filtration.

[0092] Application Example 3

[0093] The preparation method of fatty alcohol polyoxyethylene ether C8AEO10 specifically includes the following steps:

[0094] The difference between this application example and application example 2 is that C is used. 12 With C 14 The mixed alcohols were replaced with C8 alcohols, and the test results are as follows:

[0095] Mn=622, PDI=1.04. Hydroxyl value 89.20 mg KOH / g, platinum-cobalt color=9, yield=99.2%; polyethylene glycol=0.02%, C8AEO10=98.48%, free alcohol=1.02%, impurities=0.48%.

[0096] Application Example 4

[0097] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0098] The difference between this application example and application example 2 is that the 5.4 g of catalyst described in example 1 is replaced with the same mass of catalyst described in example 2.

[0099] Application Example 5

[0100] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0101] The difference between this application example and application example 2 is that the 5.4 g of catalyst described in example 1 is replaced with the same mass of catalyst described in example 3.

[0102] Application Example 6

[0103] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0104] The difference between this application example and application example 2 is that the 5.4 g of catalyst described in example 1 is replaced with the same mass of catalyst described in example 4.

[0105] Application Comparative Example 1

[0106] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0107] The difference between this comparative example and Example 2 is that the 5.4 g catalyst described in Example 1 is replaced with 1.93 g sodium hydroxide.

[0108] Application Comparative Example 2

[0109] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0110] The difference between this comparative example and application example 2 is that the 5.4 g catalyst described in example 1 is replaced with 0.72 g cobalt acetylacetonate.

[0111] Application Comparative Example 3

[0112] Fatty alcohol polyoxyethylene ether C 12-14 The preparation method of AEO10 specifically includes the following steps:

[0113] The difference between this comparative example and application example 2 is that the catalyst 5.4 g described in example 1 is replaced with the catalyst of the same mass described in comparative example 3.

[0114] Test Example 1

[0115] GPC characterization:

[0116] The molecular weight distribution (PDI) and polymer peak area ratio of the fatty alcohol polyoxyethylene prepared in each application example and application comparison were determined using a Wyatt Technology Corporation gel permeation chromatography system. The mobile phase was tetrahydrofuran; the mobile phase rate was 1 ml / min; the injection volume was 30 μl; the sample concentration was 1.0% sample g / mobile phase g; and the detector was a Shodex RI-71 differential refractive index detector.

[0117] HPLC characterization:

[0118] The purity of the fatty alcohol polyoxyethylene ethers prepared in each application example and comparative example was tested using a Shimadzu liquid chromatograph. The chromatographic column was an Agilent C18 column; column length * column inner diameter: 250 mm * 4.6 mm; packing particle size: 5 μm; detector was a differential refractive index detector RID-20A; mobile phase was pure acetonitrile; injection volume was 50 μl.

[0119] Platinum-cobalt colorimetry:

[0120] The colorimetry of the fatty alcohol polyoxyethylene prepared in the application examples and comparative examples was measured using a ColorSpectrum CS-821N high-stability benchtop spectrophotometer. For black-and-white calibration in reflectance mode, the black-and-white calibration box was placed in the test port, and the calibration button was pressed to perform black-and-white calibration. A cuvette containing pure water was placed in the transmission test port as the test liquid with a colorimetry of 0 for calibration.

[0121] The performance test results of Application Example 1 after 10 cycles are shown in Table 1 below:

[0122] Table 1

[0123]

[0124] As shown in Table 1, the binuclear cobalt complex catalyst prepared in Example 1 of this invention maintained high catalytic activity and good stability after 10 consecutive cycles. With increasing cycle number, the product yield only slowly decreased from 99.60% to 97.18%, and the PDI remained consistently between 1.04 and 1.08, indicating that the catalyst could effectively control the polymerization reaction even after multiple cycles, resulting in a narrow molecular weight distribution of the obtained product. Meanwhile, the target product C... 18 The AEO10 content remained consistently above 97.88%, the polyethylene glycol content increased only from 0.08% to 0.20%, the free alcohol content remained between 1.12% and 1.52%, and the impurity content consistently did not exceed 0.40%, indicating that the increase in side reactions during catalyst recycling was minimal, and the catalytic selectivity remained at a high level. Although the platinum-cobalt color gradually increased from 6 to 20 with increasing cycle number, it remained at a relatively low level overall.

[0125] The performance test results of Application Example 2 and Application Comparative Examples 1-3 are shown in Table 2 below:

[0126] Table 2

[0127]

[0128] As shown in Table 2, the catalysts of the present invention used in Examples 2-6 all exhibited excellent catalytic performance. The yields of the obtained fatty alcohol polyoxyethylene ether products all reached over 99%, the PDI remained at 1.04, the target product content remained above 98.32%, the polyethylene glycol content did not exceed 0.08%, the free alcohol content remained between 1.02% and 1.09%, and the platinum-cobalt color was only 7-9. This indicates that the binuclear cobalt complex catalyst of the present invention has high catalytic activity and selectivity, can effectively suppress side reactions, improve the purity of the target product, and obtain polyoxyethylene ether products with narrow molecular weight distribution and light color. Among them, the catalyst obtained in Example 4 using trifluoromethyl thioligands further reduced the product color and impurity content, indicating that changing the ligand substituents can further optimize the selectivity of the catalyst.

[0129] When sodium hydroxide was used as a catalyst in Comparative Example 1, the product yield decreased to 95.2%, PDI increased to 1.09, platinum-cobalt color increased to 32, the target product content was only 93.68%, and the free alcohol content increased to 4.02%, indicating that the traditional alkaline catalyst has poor selectivity and is prone to side reactions.

[0130] When Comparative Example 2 was catalyzed with cobalt acetylacetone, the product yield further decreased to 93.4%, the PDI increased to 1.14, the platinum-cobalt color reached 45, the polyethylene glycol content increased to 0.53%, and the impurity content reached 2.17%. This indicates that ordinary cobalt complexes are difficult to effectively control the ethylene oxide polymerization process, resulting in more side reactions and a significant decrease in product purity and quality.

[0131] When Comparative Example 3 was used with a binuclear cobalt catalyst without the -SCH3 ligand, the product yield was only 92.44%, the PDI was 1.12, the target product content decreased to 92.56%, the free alcohol content increased to 6.79%, and the polyethylene glycol content increased to 0.35%. This indicates that the methylthioligand can effectively regulate the electronic environment of the binuclear cobalt active center, improve the catalyst activity and polymerization selectivity, and reduce the formation of unreacted alcohols and byproducts. It is an important structural factor for obtaining high-performance catalysts.

[0132] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0133] The above description of the embodiments is intended to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A binuclear cobalt complex catalyst, characterized in that, The binuclear cobalt complex catalyst is composed of a binuclear cobalt complex supported on an inorganic support. The general structural formula of the binuclear cobalt complex is: [Co2(μ-CH(3-R-pz)2)2Cl2], and its molecular structure is shown below: ; In the formula, R is either -SCH3 or -SCF3.

2. The binuclear cobalt complex catalyst according to claim 1, characterized in that, The carrier is fluorapatite, the particle size of the carrier is 50~200 nm, and the cobalt loading is 3~10 wt% of the carrier mass.

3. A method for preparing a binuclear cobalt complex catalyst as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: 1) Under inert gas protection, 3-bromopyrazole was dispersed in a solvent, and sodium thiolate was added to carry out a nucleophilic substitution reaction. After post-treatment, alkylthiopyrazole was obtained. 2) In a solvent, alkylthiopyrazole and dibromomethane were subjected to an N-alkylation reaction in the presence of sodium hydroxide aqueous solution and tetrabutylammonium bromide, and after post-treatment, CH2(3-R-pz)2 was obtained. 3) CH2(3-R-pz)2 is dispersed in a solvent, and then n-butyllithium is added to carry out a deprotonation reaction to generate [CH(3-R-pz)2]. - Then [CH(3-R-pz)2] - Coordination assembly reaction with cobalt salt in solvent was carried out, and the product was filtered, washed and dried to obtain binuclear cobalt complex; 4) Fluoroapatite is degassed under vacuum, and then the binuclear cobalt complex is dispersed in a solvent under inert gas protection. Fluoroapatite is added for loading to obtain the binuclear cobalt complex catalyst.

4. The preparation method according to claim 3, characterized in that, In step 1), the sodium thiolate is either sodium methanethiol or sodium trifluoromethanethiol.

5. The preparation method according to claim 3, characterized in that, In step 1), the molar ratio of 3-bromopyrazole, sodium methanethiol, and solvent in the nucleophilic substitution reaction is 1:1~10:1~30, the reaction temperature is 60~100℃, and the reaction time is 4~12h.

6. The preparation method according to claim 3, characterized in that, In step 2), the molar ratio of 3-alkylthiopyrazole, sodium hydroxide, tetrabutylammonium bromide and dibromomethane is 1:1~10:0.01~0.1:0.1~5, and the N-alkylation reaction is carried out at room temperature for 8~20 hours.

7. The preparation method according to claim 3, characterized in that, In step 3), the molar ratio of CH2(3-R-pz)2, solvent and n-butyllithium in the deprotonation reaction is 1:200~500:1~10. The reaction conditions are as follows: in an anhydrous and oxygen-free glove box under nitrogen protection, the temperature is cooled to -60~-90℃, and the n-butyllithium solution is added dropwise with stirring. After the addition is complete, the temperature is maintained at -60~-90℃ and stirred for 10~60 minutes. Then, the temperature is naturally raised to room temperature and stirring is continued for 0.5~3 hours.

8. The preparation method according to claim 3, characterized in that, In step 3), the [CH(3-R-pz)2] in the coordination assembly reaction - The molar ratio of cobalt salt to solvent is 1:1~10:1~200, the reaction time is 5~20h, and the reaction temperature is room temperature.

9. The use of a binuclear cobalt complex catalyst as described in claim 1 or 2 in the preparation of narrowly distributed fatty alcohol polyoxyethylene ethers.

10. A method for preparing a narrowly distributed fatty alcohol polyoxyethylene ether, the method comprising the following steps: The fatty alcohol and catalyst are placed in a reaction vessel, and ethylene oxide is introduced to carry out a free radical reaction. After the reaction is completed, the narrow distribution fatty alcohol polyoxyethylene ether is obtained by post-treatment. The catalyst is characterized in that the catalyst is a binuclear cobalt complex catalyst as described in claim 1 or 2, and the amount of the binuclear cobalt complex catalyst is 0.1% to 5.0% of the fatty alcohol.